Fatty Acid Profiles in the Kernel Oils of Artocarpus odoratissimus and Litsea garciae - Zaini, Bin Assim; Firus Musfirah, Poli (Medwell Publishing, 2019)
Kernels of A. odoratissimus and L. garciae fruits collected from different areas in Sarawak were extracted and the fatty acid profiles in their kernel oils were studied. Proximate analysis of the kernels such as moisture content, ash content, crude fat and crude fiber were determined. The kernels were extracted using Soxhlet extraction apparatus and the Fatty Acid Methyl Esters (FAME) composition in the kernel oils were analysed using Gas Chromatography-Mass Spectrometry (GC-MS). The number of FAME components found in A. odoratissimus kernel oil was higher in comparison to L.garciae kernel oil. The major compound in kernel oil of each fruit sample also differs from each other; C12:0 (lauric acid) (28.75±0.09-34.12±1.02%) was the main FAME in L.garciae while C18:2n6c (linoleic acid) (37.30±4.62-40.74±6.19%) was the dominant compound in A. odoratissimus. This study is significant as it has revealed that the kernel oils of these underexploited indigenous fruits have a great potential to be developed for the applications in nutrition, industrial and cosmetics.